Christ actually : the Son of God for the secular age - Carroll, James, 1943- (Viking, 2014)
What can we believe about--and how can we believe in--Jesus Christ in light of the atrocities of the twentieth century and the drift from religion that followed? Here, James Carroll traces centuries of religious history and theology to face this core challenge to modern faith. Carroll's search is a highly personal one, beginning with a crucial received memory of Jesus that separates him from his essential identity as a Jew, and therefore as a human. The divinity of Jesus trumped his humanity, including his Jewishness. Yet if Jesus was not taken as divine, he would be of no interest to believers. Thus Carroll takes the God-man question head-on, restoring its perennial answer, but in a new way. Drawing on a wide range of scholarship as well as his own acute searching, Carroll shows how faith in Jesus evolved in the first place. His fresh reading of the Gospels reinstates the context of the Romans' effectively genocidal war against the Jews, a first Holocaust that profoundly distorted the Christian memory of Jesus. In this retrieval, the great characters in Jesus' story, from John the Baptist and Peter to Paul and the various Marys, come to life in a new context. Far from another book about the "historical Jesus," Christ Actually takes the challenges of secularism seriously. The new fact of the human condition, that we are capable now of bringing about the extinction of our species, must change the meaning of faith. Humans of all stripes continue to long for the transcendent, and it is as a figure of transcendence that Jesus Christ most compellingly stands. Finally, Carroll retrieves the power of Jesus' profound ordinariness, his simple life and his call to imitate him, all suggesting an answer to Carroll's own last question--what is the future of Jesus Christ? This book points the way. --From publisher description.